Social Class Representation in the Film Satria Dewa Gatotkaca: Representasi Kelas Sosial dalam Film Satria Dewa Gatotkaca - Hidayatullah, Barriman; Hariyanto, Didik (House of Wisdom: Journal on Library and Information Sciences, 2025)
General Background: Social class representation in films plays a significant role in shaping public perceptions of societal hierarchies. Specific Background: The film Satria Dewa: Gatotkaca integrates cultural narratives of Pandawa and Kurawa, offering a rich medium for exploring class distinctions. Knowledge Gap: Despite the prevalence of social stratification themes in Indonesian cinema, limited studies have examined them through Roland Barthes’ semiotic framework. Aims: This study analyzes the representation of social class in Satria Dewa: Gatotkaca using a descriptive qualitative approach with Barthes’ semiotic theory. Results: Analysis identified four key aspects: lifestyle disparities, differences in attire, implicit social boundaries, and class identity shaped by royal lineage. Novelty: The study extends semiotic analysis to a contemporary Indonesian superhero film, linking visual and narrative signs to socio-cultural constructs of class. Implications: Findings provide insights for media scholars and filmmakers on how cinematic signs reinforce or challenge social stratification, highlighting the role of visual storytelling in cultural discourse. Highlights: Identifies visual and symbolic cues of class in Satria Dewa: Gatotkaca. Connects royal lineage to contemporary class identity in film. Offers a semiotic framework for analyzing Indonesian popular cinema. Keywords: Representation, Roland Barthes, Semiotic, Social Class, Film Analysis